2011
DOI: 10.1088/0268-1242/26/12/125003
|View full text |Cite
|
Sign up to set email alerts
|

Annealing induced hysteresis suppression for TiN/HfO2/GeON/p-Ge capacitor

Abstract: In this paper the annealing effects in N 2 on the electrical characteristics of a TiN/HfO 2 /GeON/p-Ge capacitor are investigated. Well behaved capacitance-voltage curves were obtained for the sample annealed at 400 • C for 3 min in N 2 . A negligible hysteresis was demonstrated comparing with a hysteresis of 0.5 V for the as-deposited sample. The suppression of hysteresis is attributed to the reduction of electron traps in the dielectric layer, which is verified by the MOS pulse method. Besides, the interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…3b shows an abrupt Al/GeO x N y interface. The thickness of the amorphous GeO x N y layer is about 1 nm which agrees well with our MOS capacitors data 13,25 In contrast, the interfacial layer thickness for Al/GeO 2 /n-Ge sample seems to be about 3.5 nm, which is much larger than the data of 1-2 nm revealed in our previous MOS capacitors work using a similar passivation process. 14 For Al/GeO 2 /n-Ge contacts, it is believed that the penetration of Al into the interfacial layer is causing the failure of FL depinning.…”
Section: Resultssupporting
confidence: 91%
“…3b shows an abrupt Al/GeO x N y interface. The thickness of the amorphous GeO x N y layer is about 1 nm which agrees well with our MOS capacitors data 13,25 In contrast, the interfacial layer thickness for Al/GeO 2 /n-Ge sample seems to be about 3.5 nm, which is much larger than the data of 1-2 nm revealed in our previous MOS capacitors work using a similar passivation process. 14 For Al/GeO 2 /n-Ge contacts, it is believed that the penetration of Al into the interfacial layer is causing the failure of FL depinning.…”
Section: Resultssupporting
confidence: 91%
“…In addition, it is well documented that Ge 3 N 4 is more thermodynamically stable with highk permittivity in counter to GeO 2 . 37,38,51 Accordingly, the IL rich with Ge-N bonding rather than Ge-O compounds will exhibit a more thermally stable IL. Based on this assumption and above discussion it can be suggested that a more thermally stable IL was formed for 10 and 15 minutes oxidation/nitridation since these samples consist of more stoichiometric Ge 3 N 4 compound and F I G U R E 7 Deconvoluted Ge 3d narrow scan spectra for different oxidation/nitridation durations (5, 10, 15, and 20 minutes) fewer sub-stoichiometric GeO 2 , GeO x , and GeO than those of 5 and 20 minutes samples.…”
Section: Xps Analysismentioning
confidence: 99%
“…Consequently, the presence of a large amount Ge 2+ (GeO) and Ge 4+ (GeO 2 ) will cause sharp degradation on the thermodynamic stability of the gate stack. In addition, it is well documented that Ge 3 N 4 is more thermodynamically stable with high‐ k permittivity in counter to GeO 2 37,38,51 . Accordingly, the IL rich with Ge‐N bonding rather than Ge‐O compounds will exhibit a more thermally stable IL.…”
Section: Physical and Electrical Characterizationmentioning
confidence: 99%
See 2 more Smart Citations